Constructing an electronic fieldwork diary (EFWD) using OneNote. Issue 1 (2nd January 2017) - Tam, Ailie
ABSTRACT: A fieldwork diary (FWD) is a useful tool for capturing and reflecting on fieldwork experiences, triangulating ideas, and inciting creative thinking. Traditionally, a FWD has involved handwritten notes; however, constructing an electronic fieldwork diary (EFWD) means that notes can involve multimedia content, data can be coded and easily searched, accessed on various portable devices, and securely protected and backed up. This article shares lessons learnt from creating an EFWD using OneNote, including structuring and organising the diary, writing fieldwork notes, and tips for coding. An EFWD can be a useful tool for social science researchers or development practitioners undertaking fieldwork.